Dental Treatment Of Medically Compromised Patient - El-Beialy, Ragab Radwan R. (Saunders, USA, 2014)
This book is recommended for dental students studying human disease first in the undergraduate curriculum and subsequently in oral and maxillofacial surgery in the clinical years. It is also of value for postgraduate dental students, dental practitioners, and residents receiving training in oral and maxillofacial surgery. This book has been prepared as an update on the rapid advances in knowledge. This book contains information obtained from authentic, recent and highly regarded sources. A wide variety of references are listed and the text includes only reliable data and information. A large portion of the text deals not with drugs but with the management of the case in a broader sense. It focuses on the signs and symptoms of systemic diseases and strengthens further especially those areas of practical concern to all dental surgeons, such as the problems associated with a bleeding tendency, cardiac, liver, kidney, hormonal problems and other transmissible diseases including HIV, and immunosuppressive treatment